Evaluation of the phytoremediation potential of T. spathecea and P. balforiana grown in crude oil polluted soils - Pius Adah; Ndem Enyogor Edu; Kogbara B. Henry; Reagan B. Agbor; Gabriel I. Abu; Nsude L. Odinakachukwu; Jude I. Isorshe (Center for Science and Technology, IAIN Surakarta, 2024)
The impact of crude oil contamination on the environment, especially on soil quality, has been a major concern in Nigeria and for regulatory bodies worldwide. This study focused on assessing the phytoremediation potential of two plant species T. spathecea and P.balfouriana, grown on crude oil-contaminated soils. The plant were cultivated in soils polluted with crude oil at concentrations of 0, 50, 100, 150 and 200 mL/kg. The research was laid out in a 5 x 5 factorial experiment with three replicates, in a completely randomized designed to give a total of 75 experimental units. The gas chromatographic flame ionization detector (GC-FID) was used in determining the total petroleum hydrocarbon (TPH), the atomic absorption spectrophotometer (AAS) was used to determine the heavy metals. The relevant analytical techniques of APHA and AOAC (2020) was used to determine the phytochemical contents of the plant species. The results of TPH analysis revealed that the concentration of TPH increased with the rising concentration of crude oil pollutant in the soil. TPH values were 1,120 mg/kg for P. balfouriana and 2,762.79 mg/kg for T. spathecea. Both plant species showed considerable growth despite increasing crude oil concentrations. The results of heavy metals phytoextraction indicated a trend of increasing metal concentrations with increasing crude oil pollution. Copper concentration ranged from 2.28 mg/kg in T. spathecea to 12.64 mg/kg in R. simplex. Iron uptake ranged from 11.36 mg/kg in P. balfouriana to 22.40 mg/kg T. spathcea. The uptake of manganese increased from 5.56 mg/kg in P. balfouriana to 10.56 gm/kg in T. spathecea, while cobalt concentration decreased from 0.08 mg/kg in T. spathecea to 0.04 mg/kg in P. balfouriana. The study highlights the potential of P. balfouriana and T. spathecea for phytoremediation in crude-contaminated soils and advocates for their use as effective tools for soil remediation.